Crystallography of Martensitic Transformation in Epitaxial Ni50Mn30Ga20 Thin Film. Issue 4 (6th July 2017) - Yang, Bo; Liu, Tingting; Hao, Xiao Wen; Li, Zong Bin; Zhang, Yu Dong; Qin, Gao Wu; Philippe, Marie‐Jeanne; Esling, Claude; Zhao, Xiang; Zuo, Liang
Abstract : In the present work, scanning electron microscopy and electron backscatter diffraction technique revealed that the microstructure of epitaxial Ni50 Mn30 Ga20 thin films are composed of six different orientated NM martensite variant colonies. In each martensite variant colony, there are eight different orientated NM martensite variants. The six NM and 7M martensite variant colonies are transformed from six (101)A planes of austenite, with the transformation consequence from Austenite to 7M martensite and then to NM martensite. Cross section TEM examination reveals the coexistence of 7M martensite and NM martensite. The habit plane between 7M martensite and NM martensite can be determined as (001)mono of 7M martensite and (112)Tetr of NM martensite. Abstract : EBSD characterization and crystallographic calculation indicates that the martensitic transformation sequence is from Austenite to 7M martensite and then to NM martensite (A → 7M → NM) in the Ni50 Mn30 Ga20 thin films. Cross section TEM images presents the coexistence of 7M and NM martensite and the habit plane between the 7M and NM martensite.